Studi Kelayakan Proses Pengelasan Smaw Dan Fcaw Di Pt. Dok Jmi Semarang Dari Aspek Teknis Dan Ekonomis - Sugeng Haryadi; Sunu Arsy Pratomo (Fakultas Teknik Universitas Cenderawasih, 2023)
The development of welding technology in this era took place rapidly, especially in the sector of new ship building and ship construction repair. Incorrect welding activities often cause delays which cause costs, time and consumables losses. In order to develop the speed and efficiency of the welding work, it is mandatory to determine a welding method that is suitable for the site conditions. This study provides a choice of three welding methods consisting of the SMAW and FCAW welding methods based on their strength and economic value. To strengthen the results of welding can be tested with a destructive test consisting of a tensile test, bending test and impact test. Next, the calculation of the welding cost per kg, welding speed per meter and electrode consumption is carried out to find out the difference in the economic value of all the welding materials. When tested, it was found that there was no difference in tensile strength between SMAW and FCAW. Welding method, maximum 1%, but SMAW welding method has 4% better yield strength than FCAW welding method. The ductility value of the FCAW welding method is 34% better than the SMAW welding method. The FCAW welding method has 67% better economic value when compared to the SMAW welding method. The FCAW welding method has a speed of 72% better than the SMAW welding method, and the FCAW welding method is 50% more efficient than the SMAW welding method.